Proteomics and phosphoproteomics reveal novel proteins involved in Cipangopaludina chinensis carcasses - Liu, Gongzhen; Zhong, Kangyu; Gong, Shanmin; Li, Xinru; Li, Yanshen (Frontiers in Chemistry, 2024)
Cipangopaludina chinensis is a common freshwater mollusk that is widely distributed worldwide, especially in China. In our research, 1,382 proteins and 1,039 phosphorylated proteins were identified from C. chinensis carcasses, and 690 differentially expressed proteins (DEPs) were quantified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that the DEPs are involved in cellular processes, single-organism processes, metabolic processes, developmental processes, localization, and biological regulation. The phosphorylated proteins were found to be related to the Rap1 signaling pathway, Ras signaling pathway, calcium signaling pathway, and longevity-regulating pathways. Moreover, we also identified important regulatory enzymes, such as guanylate cyclase, tyrosine protein kinase, receptor protein tyrosine kinase, and glyoxylate reductase/hydroxypyruvate reductase. Notably, we found guanylate cyclase to be present in multiple signaling pathways, including the Rap1 signaling pathway, calcium signaling pathway, Ras signaling pathway, insulin secretion, longevity regulating pathway, glutamatergic synapse, circadian entrainment, and gap junction. This enzyme may play a crucial role in regulating molecular mechanisms in C. chinensis. In summary, proteomic and phosphoproteomic analyses of C. chinensis carcasses displayed significant differences among different geographical isolates, which helps enhance our understanding of food nutrition, signaling pathways, and metabolic mechanisms in C. chinensis.